Acculturation of Local Culture in the Celebration of the Maulid Nabi in Indonesia: A Study of the Ambelu Tradition from the Perspective of the al-Shafi'i and Hanafi Madhhab - Jubba, Hasse; Galib, Syamsul Arif; Yuktikarini, Devi Dharma; Asti, Mulham Jaki (Universitas Islam Negeri Alauddin Makassar, 2024)
This study analyses the acculturation of Islam to the Ambelu tradition in the celebration of the Maulid Nabi in Bontomanai Subdistrict, Selayar Islands Regency through a comparison of the views of the al-Shafi'i and Hanafi Madhhab. This study aimed to examine whether this practice correlated with Islamic law or contained elements of bid'ah and to assess how local cultural acculturation influenced the implementation of the tradition in the context of religious celebrations. A qualitative method with a descriptive-analytical approach was used in this study. Data collection included direct observation, interviews with religious leaders and local communities, as well as a review of related documents. The analysis was further carried out by comparing the perspectives of the al-Shafi'i and Hanafi Madhhab on the Ambelu tradition and the concept of bid'ah in Islam. The results showed that the Ambelu tradition was widely accepted by the local community as part of religious culture, despite various opinions among scholars regarding the legal status. The al-Shafi'i Madhhab tended to be more permissive of this practice, while the Hanafi Madhhab adopted a more cautious stance in the context of bid'ah. This study was original in the comparative analysis of two fiqh madhhab in examining local traditions that rarely receive academic attention. Additionally, it also offered fresh insights into the interaction between Islamic law and local culture in Selayar. The results emphasized the importance of a contextual method to studying local traditions in Islam and outlined the relevance of maintaining harmony between culture and religion in society.